Rancang Bangun Sistem Informasi Pengolahan Data Pasien Pada Klinik Pratama Umi Rahma Bekasi Berbasis Web - Novita Indriyani (LPPM Universitas Bina Sarana Informatika, 2018)
Pratama Umi Rahma Clinic is located at Jalan Asem Jaya No. 116, which is engaged in health. he problems that occur at the Pratama Umi Rahma Clinic are the patient data processing system contained in the Pratama Umi Rahma Clinic, which is currently still carried out with a manual recording system and in making and giving ineffective and efficient reports. Researchers aim to examine and help solve problems faced by Umi Rahma Primary Clinic, namely by designing a patient data management information system. he method used in the construction of information systems at the Pratama Clinic Umi Rahma is using the Rapid Application Development (RAD) method to facilitate the writer in building and developing systems and using Unified Modeling Language (UML) modeling using the Java programming language. The information system created is expected to help the Pratama Umi Rahma Clinic in improving health services and organizational performance, as well as in the administration section as a patient data processor.